2014
DOI: 10.1242/jeb.105353
|View full text |Cite
|
Sign up to set email alerts
|

Host orientation using volatiles in the phoretic nematode Caenorhabditis japonica

Abstract: Host orientation is the most important step in host-searching nematodes; however, information on direct cues from hosts to evoke this behaviour is limited. Caenorhabditis japonica establishes a species-specific phoresy with Parastrachia japonensis. Dauer larvae (DL), the non-feeding and phoretic stage of C. japonica, are predominantly found on female phoretic hosts, but the mechanisms underlying the establishment of this phoresy remain unknown. To determine whether C. japonica DL are able to recognize and orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been shown that dauer stage Caenorhabditis spp. are attracted to certain insect species, increasing the opportunity to engage in phoresis [57]. This cluster of shared srsx GPCRs may therefore mediate this attraction, in isolation, or in synergy with other such receptors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that dauer stage Caenorhabditis spp. are attracted to certain insect species, increasing the opportunity to engage in phoresis [57]. This cluster of shared srsx GPCRs may therefore mediate this attraction, in isolation, or in synergy with other such receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that new habitat and substrate types will be discovered in the future, especially if sampling efforts go beyond France, Germany, the UK, and the US, where most previous collections were made. Compared to other Caenorhabditis species such as C. japonica (Yoshiga et al 2013; Okumura and Yoshiga 2014) or C. drosophilae (Kiontke 1997), the species C. elegans does not appear to have a highly specialized habitat nor a highly specialized biotic association with larger invertebrates. Although much remains to be discovered, C. elegans seems to have a more generalist lifestyle, which appears similar to that of some other Caenorhabditis species such as C. briggsae or C. remanei (see possible competition relationships in Possible competitors ).…”
Section: Habitats and Substratesmentioning
confidence: 95%
“…, feeding on the decomposing host after it dies) underlies the association (Kiontke and Sudhaus 2006). More specific relationships with invertebrate hosts are known, for example for the nematode Pristionchus pacificus , which in part lives in association with scarab beetles (Sommer and McGaughran 2013), or C. japonica , which shows a phoretic interaction with the bug Parastrachia japonensis (Yoshiga et al 2013; Okumura and Yoshiga 2014). In the case of C. elegans , more details on the specificity of the interaction would now require specially designed studies, such as life history assays on the host or collection of dead hosts from the wild (beyond one anecdotal report in Barrière and Félix 2007).…”
Section: Macroscopic Invertebrates As Possible Vectors or Hostsmentioning
confidence: 99%
“…The IJ dispersal stage of parasitic nematodes is similar to dauer in several ways: Both are nonfeeding stages with a resistant cuticle (67), and both recognize and exploit carriers/hosts similarly (18,68). One gene class that has been shown to affect dauers and IJs is the neuropeptide-encoding set of genes (27,48).…”
Section: Peptidergic Signaling Downstream Of Sbt-1 Promotes Dauer Entmentioning
confidence: 99%